Group Exhibition-Memory, Installations exhibition, Apollonia Venue and Projected Visions, Video Art Palais du Rhin/Drac Alsace, Strasbourg - Antoniou, Klitsa (My University, 2026)
Memory, Installations exhibition, Apollonia Venue and Projected Visions, Video Art Palais du Rhin/Drac Alsace, Strasbourg, France Curated by Demetris Costantinides